Revitalizing physical assessment in undergraduate nursing education - what skills are important to learn, and how are these skills applied during clinical rotation? A cohort study - H. Ösp Egilsdottir; Kirsten Røland Byermoen; Anne Moen; Hilde Eide (BMC, 2019)
Abstract Background The preparedness of newly graduated registered nurses for a demanding work environment and care practices takes form during nursing education. Norwegian nursing education at one university has implemented a selection of basic physical assessment skills (B-PAS) in the nursing curriculum in order to prepare nursing students for a demanding work environment post-graduation. Methods A mixed-method cohort design. We evaluated nursing students' self-reported use of B-PAS during their clinical rotation using the "Survey of Examination Techniques Performed by Nurses" questionnaire (30 items). In addition, two focus group interviews elicited factors that hinder or facilitate the actual use of B-PAS during clinical rotation. We recruited students from a bachelor's degree programme for nursing at a Norwegian university. Three hundred and sixty-three of 453 eligible nursing students in the first, second, and third year of the bachelor's degree programme participated in the study (80%). Results ANOVA showed a significant progression (p < 0.016) in students' self-reported use of B-PAS. Auscultation and percussion skills were graded below the median score of 3, which indicates that these skills were less used throughout the programme. The nursing students highlighted contextual factors for their use of B-PAS when in clinical rotation. Preceptors are important gatekeepers for successful implementation, and there is a need for close collaboration between the university and clinical practice. Conclusion Despite the reduced PAS taught in the curricula, there is still a lack of application of such skills in clinical rotations. This study highlights that research should explore how different work environments influence the utilisation of learned skills, and which learning strategies are appropriate or most successful for stimulating clinical reasoning and the extensive use of physical assessment.